Saccharomyces cerevisiae deletion strains with complex DNA content profiles. Issue 1 (19th June 2013) - Hoose, Scott A.; Trinh, Jimmy T.; Leitch, Margaret Camille; Kelly, Michelle M.; McCormick, Ryan F.; Spyrou, Constantine L.; Smith, Roger; Polymenis, Michael
Abstract To identify Saccharomyces cerevisiae genes required for the proper timing of cell cycle transitions, we previously reported a systematic examination of the DNA content of homozygous diploid deletion strains. However, deletion strains with complex DNA content profiles were not examined in that study. Here, we report S. cerevisiae genes that when deleted give rise to DNA content profiles consistent with roles of the corresponding gene products during DNA replication. We also identified a set of genes whose deletion leads to increased DNA content, consistent with defects in mitosis, cytokinesis, or cell separation. Finally, we examined known interactions between the gene products of each group, placing these gene products in functional networks. Taken together, the data we present further validate the roles of the corresponding gene products in these processes, facilitating efforts to delineate gene function critical for genome replication, maintenance, and segregation.